Killer keepsakes [large type] - Cleland, Jane K. (Cleland, Jane K. Josie Prescott antiques mysteries., 2009)
One of the mainstays of Prescott's Antiques and Appraisals has always been the cheerful and helpful assistant, Gretchen, who turned up unexpectedly just as Josie was setting up shop in New Hampshire. Gretchen has always been so dependable that it seems odd when she doesn't show up for work one day. Surprise turns to alarm when a dead body is found in Gretchen's house, and she's the prime suspect. How much does Josie know about Gretchen, anyway? Enough to believe she isn't capable of murder ...